Autotrophic metabolism considered to extend the applicability of the carbon balances model for assessing biodegradation in petroleum-hydrocarbon-contaminated aquifers with abnormally low dissolved inorganic carbon. (10th July 2020) - Cai, Pingping; Ning, Zhuo; Zhang, Min; Guo, Caijuan; Niu, Manlan; Shi, Jiansheng
Abstract: The carbon balance model has been used as a general method to assess biodegradation in petroleum hydrocarbon-contaminated (PHC) aquifers for two decades. The model assumes that heterotrophic metabolism is the dominant process for degrading hydrocarbon to CO2 . Another important metabolic process that autotroph consumption of CO2 is usually considered to be negligible. However, a phenomenon of abnormally low dissolved inorganic carbon (DIC) was found in the North China Plain. According to the biodegradation mechanism, the existing model encounters the problem and only the consideration of autotrophic metabolism can explain the phenomenon. Therefore, in this paper, the carbon balance model was extended to four specific processes "heterotrophic metabolism (H)→ heterotrophic metabolism with precipitation (HP) → autotrophic metabolism (A) → autotrophic metabolism with precipitated (AP)". Using the model, measurements of biodegradation at three time points over two years were 2.02, 1.46 and 1.36 (×10 5  mol.a −1 ) respectively, close to another common method of terminal electron acceptors (TEAs) method (1.93, 0.71, and 1.34 (×10 5  mol.a −1 )). Moreover, supported by the δ 13 C of DIC values and, metagenomics data, this developed model was evaluated to be reliable. Given that PHC sites are widespread, the developed model can give more accurate carbon emission estimation for climatic change evaluation and is significant for the environmental communication for energy utilization. Graphical abstract: Image 1 Highlights: An autotrophic metabolism model that considers carbon balance was developed. A calculation method for biodegradation assessment based on the model was developed. The developed model was verified to be reliable according to various evidences. The model developed in a PHC aquifer is meaningful for carbon emission estimation.